Overweight management: A cross-sectional study with special insight on metformin use in obesity control - Safa’a Ali Al-Qudah, Khawla Damen Al-Hamaideh, Isra Mahmoud Dmour, Samar Sameer Al Sbaihi (Journal of Applied Pharmaceutical Science, 2022)
The aim of the current study is to assess the attitudes and behavior of the Jordanian public toward weight management and to compare their different approaches to weight loss with a special emphasis on metformin’s role in weight reduction. This is a questionnaire-based study completed by 574 Jordanians. The results showed that 78.2% of the participants were overweight despite the different approaches used by Jordanians for weight management, including diet (64.8%), exercise (47.7%), and herb use (20.2%), in addition to the use of medications and dietary supplements (16.6% and 12.4%, respectively). It was found that 40.6% of the study sample used metformin for different causes, including weight control (19.3%). About 40% noticed weight loss in different ranges of kilograms at different durations of time, while more than half of the users (54.5%) did not notice any weight loss. 32.2% used diet while using metformin for weight loss compared to 50.2% that used exercises in addition to metformin for control of weight. In conclusion, being overweight is a health problem in Jordan. Lifestyle changes, including diet and exercise, were the most adopted approaches by the Jordanians for weight loss. Besides, different weight reduction responses to metformin were verified, and further clinical studies are needed to evaluate the exact weight reduction effect of metformin.
Keywords: Metformin, obesity, overweight, weight loss, Jordan